PARTISIPASI MASYARAKAT DALAM PENANGANAN COVID-19 DI DESA TOMBATU TIGA TENGAH KECAMATAN TOMBATU UTARA KABUPATEN MINAHASA TENGARAH - MOKOROWU, SYOVI; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2022)
The purpose of this study is to deal with community participation in dealing with the covid-19outbreak to break the chain of covid-19 in the middle tombatu three village in response to the governmentregulation of Law No. 4 of 1984 as a guide for the community in the middle tombatu three village to worktogether in facing Covid-19 and to comply with government regulations so that not many people are affectedby COVID-19 in the village of Tombatu Tiga Tengah and carry out the health protocols that have beenregulated by the regional government. this research method is descriptive qualitative. The result of thisresearch is that the Covid-19 handler analyst in the village of Tombatu Tiga is responding to the governmentregulation Law No. 4 of 1984 concerning infectious outbreaks. The results obtained are that the analysis ofthe participation in handling covid-19 in the village of Tombatu Tiga Tengah has been successfully carriedout but there are still obstacles that occur such as many people who neglect to comply with health protocolsand how much assistance has not been distributed to the community and there are still concessions thatoccur. in health protocols.Keywords : participation in handling Covid-19